2002
DOI: 10.3346/jkms.2002.17.1.81
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Concentrations of Formalin on Paw Edema and Pain Behaviors in Rats

Abstract: The aim of this study was to determine whether formalin reliably provokes a paw edema and pain behavior. The paw of male Sprague-Dawley rats were injected with 100 microliter of formalin with 2.5% (F2.5), 5% (F5), and 10% (F10) concentrations. Following the formalin (n=8) or saline (control, n=6) injection, the flinching or licking of the paw was recorded for the phase 1 response (0-5 min after injection) and phase 2 response (20-60 min). The formalin-induced paw edema was assessed by measuring the diameters o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
37
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 18 publications
5
37
0
Order By: Relevance
“…In this model, formalin is able to acutely affect peripheral sensory nerve endings (5), with subsequent release of mediators, which give rise to a biphasic painful response (3,16). However, when Dubuisson and Dennis (1) first described this response, they had also observed that inflammation (edema) was a prominent feature accompanying the painful response, later confirmed by others (4,17).…”
Section: Discussionmentioning
confidence: 94%
“…In this model, formalin is able to acutely affect peripheral sensory nerve endings (5), with subsequent release of mediators, which give rise to a biphasic painful response (3,16). However, when Dubuisson and Dennis (1) first described this response, they had also observed that inflammation (edema) was a prominent feature accompanying the painful response, later confirmed by others (4,17).…”
Section: Discussionmentioning
confidence: 94%
“…A formalin concentration of 2.5-5% is a better dose than 10% because it evokes maximal responses [20]. In fact, the 10% formalin is not recommended for a pain test.…”
Section: Discussionmentioning
confidence: 99%
“…Substance P, glutamate and bradykinin are thought to participate in this phase, which is believed to be non-inflammatory pain [28]. The second phase, commonly denominated late or inflammatory phase (from 15 a 30 min) [29] is associated with the release of local endogenous mediators (histamine, serotonin, prostaglandins and bradykinin) responsible for sensitization of primary and spinal sensory neurons and subsequent activation of the nociceptor [20,25,34]. It is well established that both phases of the formalin test can be inhibited by centrally acting drug, such as narcotics, whereas peripherally acting drugs, such as acetylsalicylic acid, only inhibit the second phase [21,22,29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Intraplantar injection of formalin has been reported to produce a distinct biphasic nociceptive response [12,21], termed first and second phases [20]. The first phase, commonly denominated early or neurogenic phase (from 0 to 5 min after injection formalin) results from a direct stimulation of nociceptors (predominantly C-fibres) [22,23,27,28,31,32,34]. Substance P, glutamate and bradykinin are thought to participate in this phase, which is believed to be non-inflammatory pain [28].…”
Section: Discussionmentioning
confidence: 99%